2019
DOI: 10.1017/s1751731119001800
|View full text |Cite
|
Sign up to set email alerts
|

Review: The roles and functions of glutamine on intestinal health and performance of weaning pigs

Abstract: The gut is composed of a single layer of intestinal epithelial cells and plays important roles in the digestion and absorption of nutrients, immune and barrier functions and amino acid metabolism. Weaning stress impairs piglet intestinal epithelium structural and functional integrities, which results in reduced feed intake, growth rates and increased morbidity and mortality. Several measures are needed to maintain swine gut development and growth performance after weaning stress. A large body of evidence indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
49
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 59 publications
1
49
0
1
Order By: Relevance
“…These results demonstrated that the function for nutrient absorption in the intestine of piglets was impaired in the weaning process. Weaning stress includes dietary and environmental transitions, and separation from the dam has been demonstrated to disrupt antioxidant defense capacity and cause oxidative stress in piglets (Yin et al, 2014;Ji et al, 2019). In the present study, DEGs related to the oxidation-reduction process and oxidoreductase activity were identified by GO enrichment analysis, which may elucidate the molecular mechanisms of oxidative stress induced by early weaning.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…These results demonstrated that the function for nutrient absorption in the intestine of piglets was impaired in the weaning process. Weaning stress includes dietary and environmental transitions, and separation from the dam has been demonstrated to disrupt antioxidant defense capacity and cause oxidative stress in piglets (Yin et al, 2014;Ji et al, 2019). In the present study, DEGs related to the oxidation-reduction process and oxidoreductase activity were identified by GO enrichment analysis, which may elucidate the molecular mechanisms of oxidative stress induced by early weaning.…”
Section: Discussionmentioning
confidence: 82%
“…Previous studies have demonstrated that glutamine plays a critical role in maintaining multiple important functions, such as nutrient metabolism, immune response, and intestinal integrity, as well as the synthesis of other bioactive compounds (Li et al, 2018). Therefore, glutamine supplementation in weaning piglets may be an effective way to improve growth and maintain gut health (Wang et al, 2008;Ji et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that glutamic acid (GLU) is a non-essential amino acid that is abundantly present in the body and plays an essential function in cellular metabolism and immune responses [5]. The GLU is a precursor for protein synthesis and has been attracting attention for its diverse metabolic functions in weaned pigs [6,7]. Moreover, GLU is an important precursor for intestinal formation and immune system in the small intestine and can contribute to the immediate effect on nutrient absorption [7].…”
Section: Introductionmentioning
confidence: 99%
“…Intestinal diseases in childhood can lead to anemia, malnutrition, and impaired mental skills, which are hazardous to long-term life quality [11,12]. In livestock production, intestinal damage in young animals results in decreased growth rates and increased morbidity and mortality [13].…”
Section: Introductionmentioning
confidence: 99%